Beginsels en metodes vir die bepaling van die ouderdom van hominied fossiele en hulle vindplekke - Aardt, W. J. van (Koers, 2006)
Principles and methods used for the determination of the age of hominid fossils and their discovery sites Paleoanthropologists have an array of physical dating methods developed by researchers in the physical sciences. These techniques permit students of hominid evolution and associated culture to have increasing confidence that the evidence of past hominid morphology as expressed by the fossil finds is being placed in the correct chronological order. This article explains in a simple and straightforward way the evidence and logic that have led scientists to conclude that hominid fossils are not a few thousand years but at least several million years old. The main focus is on the 40Ar/ 39Ar technique, but other absolute dating techniques such as carbon-14, uranium-thorium-lead and radiocalcium are also reviewed. Relative dating methods are briefly discussed together with paleomagnetism (geomagnetism), optic stimulated luminescence and amino acids.